Efektivitas Problem Based Learning dalam Meningkatkan Kompetensi Siswa pada Pelajaran Perbaikan Peralatan Listrik - Yogi Dio Pratama; Usmeldi Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This research aims to determine the effectiveness of the Problem Based Learning learning model to improve the competence of class XII TITL students at SMK Negeri 5 Padang. Student learning outcomes are still low caused by teaching factors that are still teacher-centered so that students are not actively involved in the learning process in the classroom. Therefore, it is necessary to conduct research with the application of the Problem Based Learning model to see the effectiveness of students' competence in the cognitive domain. This study uses an experimental research type which is categorized into a pre-experimental research design with a one-group pretest posttest design. The subjects of this study were students of class XII TITL 1 SMK Negeri 5 Padang in the academic year 2022/2023 which consisted of 26 students. To measure this effectiveness, a pretest was given before the implementation of Problem Based Learning to measure students' initial abilities. Then the posttest was given after the learning process of Repair of Electrical Equipment after the implementation of the Problem Based Learning model. The results of the pretest and posttest will be analyzed using classical completeness testing and effect size. The test results show that the value of the students who applied the Problem Based Learning model was higher than the students who did not apply the Problem Based Learning model. Student learning outcomes after implementing Problem Based Learning increase, so that Problem Based Learning is effective for increasing student competence.